Bringing Back the States: A Congressional Perspective on the Fall of Slavery in America. Issue 4 (September 2014) - Glass, Maeve Herbert
<x xml:space="preserve">Abstract</x> In the aftermath of America's Civil War, national lawmakers who chronicled the fall of slavery described the North as a terrain of states whose representatives assembled in Congress, as evidenced in Henry Wilson's The Rise and Fall of the Slave Power in America (1872–77) and Alexander Stephens's A Constitutional View of the Late War Between the States (1868–70). Beginning in the early 1900s, scholars who helped establish the field of American constitutional history redescribed the national government as the voice of the Northern people and the foe of the states, as evidenced in Henry Wilson's The Rise and Fall of the Slave Power in America (1872–1877) and Alexander Stephens's A Constitutional View of the Late War Between the States (1868–1870), a first generation of scholars writing during the Progressive Era redescribed the national government as the voice of the Northern people and the foe of the states, as evidenced in William A. Dunning's Essays on the Civil War and Reconstruction (1898), John W. Burgess's The Civil War and the Constitution (1901–1906), and James G. Randall's Constitutional Problems Under Lincoln (1926). Although a second generation of scholars uncovered traces of the lawmakers' perspective of states, new efforts in the wake of the civil rights movement to understand the internal workings of political parties and the contributions of ordinary Americans kept the study of national lawmakers and their states on the margins of inquiry, as evidenced in leading revisionist histories of Reconstruction, including Harold Hyman's A More Perfect Union: The Impact of the Civil War and Reconstruction on the Constitution (1973), Michael Les Benedict's A Compromise of Principle: Congressional Republicans and Reconstruction, 1863–1869 (1974a), and Eric Foner's Reconstruction: An Unfinished Revolution (1988). Today, the terrain of Northern states remains in the backdrop, as illustrated in recent studies featuring the wartime national government, including James Oakes's Freedom National: The Destruction of Slavery in the United States, 1861–1865 (2012) and Mark E. Neely, Jr.'s Lincoln and the Triumph of the Nation: Constitutional Conflict in the American Civil War (2011), as well as studies of the mechanisms of constitutional change during Reconstruction, including relevant sections of Bruce Ackerman's We the People II: Transformations (1998) and Akhil Reed Amar's America's Constitution: A Biography (2005). This review essay argues that incorporating the states back into this century‐old framework will open new lines of inquiry and provide a more complete account of federalism's role in the fall of slavery. In particular, a return to the archives suggests that in the uncertain context of mid‐nineteenth‐century America, slavery's leading opponents in Congress saw the Constitution's federal logic not simply as an obstacle, but as a crucial tool with which to mobilize collective action and accommodate wartime opposition at a time when no one could say for sure what would remain of the United States.